Effectiveness of Different Treatment Modalities in Postmenopausal Women with Osteopenia and Osteoporosis - Berfu Demir; Enis Özkaya; Nilgün Öztürk; Burak Karadag; Ali Haberal (Medical Network, 2009)
OBJECTIVE: The aim of this study was to evaluate the efficacy of different antiresorptive agents and hormone therapy (HT) on T score and to compare their effectiveness with each other. STUDY DESIGN: Medical records of 1073 postmenopausal women were reviewed. Patients were classified into four groups; hormone therapy, antiresorptive therapy (AT), combined HT and AT and control. Groups were evaluated with their response to treatment modality by measuring the changes on T score. Also, patients of HT and AT groups were compared with each other according to the effectiveness of the treatment on T score changes. RESULTS: Treatment related increase in T score was significantly different in HT-AT and AT groups compared with the HT group (P=0.001, P=0.001). Within the HT group (estrogen: 170, estrogen-progestin: 234, tibolone: 136) the alteration on T score was statistically significant compared to the control group (P=0.001, P=0.001, P = 0.001). Within the AT group (etidronate: 165, alendronate: 94, risedronate : 11, calcitonin: 10) all agents were significantly different compared to the control group according to the alterations on T score (P=0.001, P=0.001, P=0.001, P = 0.001). When the change in T score was compared, the alendronate group was significantly different than the etidronate group (P=0.001). CONCLUSION: Hormone therapy combined with AT and AT alone was found to be superior to HT in terms of increments in T score values in postmenopausal women with osteopenia and osteoporosis.